A Training Program for Pharmacy Students on Providing Diabetes Care - Wongwiwatthananukit, Supakit (American Journal of Pharmaceutical Education, 2013)
Objective. To compare second- and third-year pharmacy students’ competence, attitudes, and self-confidence in providing diabetes care before and after completing a hand-on diabetes training program and to determine if the program had an impact on students’ attitude and self-confidence based on their year in the curriculum. Design. The program included classroom lectures and hands-on learning sessions in 5 facets of diabetes care. Pre- and post-test instruments measured students’ competence, attitudes, and confidence in diabetes care. Assessment. Students’ competence and the mean overall confidence score significantly improved after completing the program, while mean overall attitude score did not. Third-year students had significantly higher confidence scores than did second-year students on both pre- and post-program tests. No significant difference was found for attitude scores between second- and third-year students. Conclusion. The hands-on learning program was an effective approach to training pharmacy students in diabetes care, improving both their competence and confidence.